From Quiescence to Activation: The Reciprocal Regulation of Ras and Rho Signaling in Hepatic Stellate Cells - Saeideh Nakhaei-Rad; Silke Pudewell; Amin Mirzaiebadizi; Kazem Nouri; Doreen Reichert; Claus Kordes; Dieter Häussinger; Mohammad Reza Ahmadian (Cells)
Chronic liver diseases are marked by persistent inflammation and can evolve into liver fibrosis, cirrhosis, and hepatocellular carcinoma. In an affected liver, hepatic stellate cells (HSCs) transition from a quiescent to an activated state and adopt a myofibroblast-like cell phenotype. While these activated cells play a role in supporting liver regeneration, they can also have detrimental effects on liver function as the disease progresses to fibrosis and cirrhosis. These findings highlight the dynamic switching between different signaling pathways involving Ras, Rho GTPases, and Notch signaling. Notably, two specific members of the Ras and Rho GTPases, Eras and Rnd3, are predominantly expressed in quiescent HSCs, while Mras and Rhoc are more abundant in their activated forms. In addition, this study highlights the critical role of cytosolic Notch1 in quiescent HSCs and Rock in activated HSCs. We hypothesize that distinct yet interdependent intracellular signaling networks regulate HSC fate decisions in two key ways: by maintaining HSC quiescence and homeostasis and by facilitating HSC activation, thereby influencing processes such as proliferation, transdifferentiation, and mesenchymal transition. The proposed signaling model, combined with specific methodological tools for maintaining HSCs in a quiescent state, will deepen our understanding of the mechanisms underlying chronic liver disease and may also pave the way for innovative therapies. These therapies could include small molecule drugs targeting Ras- and Rho-dependent pathways.